The main square of Salamanca in the urbanism of the 20th century (Ciudades, 2017)
Through a diachronic vision of the Main Square of Salamanca in the 20th Century, the contemporary urban and urban planning processes, that have coexisted with the Main Square of Salamanca, and the perception of centrality that it owns, are here expounded, by means of a discourse structured in ten meditations, through a diachronic vision of the Main Square itself of Salamanca in the 20th Century. The Main Square of Salamanca was declared part of the World Heritage in 1988. Its characteristics of urban centrality, since 1755, widely known in all Latin America have influenced in the construction and usage of the rest of the prospective city, since then. It is an excellent observatory of the social relations as well as a permanent and dynamic urban “living room”.
Keywords: main square; urban history; historical heritage; monument; World Heritage; urbanism; ICOMOS-UNESCO